Late Effects in Children and Adolescents with Osteosarcoma - Bielack, Stefan S.; Hecker-Nolting, Stefanie; Beck, Johannes (Springer International Publishing, 2020)
Multimodal osteosarcoma therapy according to past and current European and American protocols is described. This includes both local treatment (usually surgery) and systemic antineoplastic therapy, which is often based on high-dose methotrexate, doxorubicin (Adriamycin), cisplatin, and sometimes ifosfamide. As all must be employed at relatively high doses, early and late adverse effects have long been a major research focus. Their long-term late effects on organ function are described, and recommendations for lifelong follow-up are given. These are meant to comply with the evidence-based recommendations of the International Guideline Harmonization Group. Follow-up after surgery of the primary tumor and (endoprosthetic) reconstruction require the expertise of specialized centers.
CRIS-Team Scopus Importer:2024-12-16
Keywords: International Guideline Harmonization Group; Long-term late effects follow-up; Multimodal therapy; Osteosarcoma